The potential of low energy earth pipe cooling in hot and humid Malaysia - Sanusi, Aliyah Nur Zafirah; Shao, Li; Ibrahim, Md. Najib (2012)
This paper presents a study on the performance of Low Energy Earth Pipe Cooling in Malaysia which has hot and humid climate throughout the year. The increasing demand of air-conditioning for cooling purposes motivates this investigation in search for better cooling alternative. The passive technology, where the ground was used as a heat sink to produce cooler air, has not been investigated systematically in hot and humid countries. Therefore, in this work, air and soil temperatures were measured on a test site in Kuala Lumpur. At 1m underground, the result is most significant, where the soil temperature are 6oC and 9oC lower than the maximum ambient temperature during wet and dry season, respectively. Polyethylene pipes were then buried around 0.5m, 1.0m and 1.5m underground and temperature reduction between inlet and outlet were compared in two different seasons; wet and dry seasons. A significant temperature reduction was found in these pipes: up to 6.4oC and 6.9oC depending on the season of the year. The results have shown the potential of Earth Pipe in providing low energy cooling in Malaysia. The temperature reduction is enough to help reduce escalating energy consumption in Malaysia.